Should we Dispense with the Idea of Personhood?: The Impoverishment of Philosophical-Theological Language - Colen, José-A. (Scripta theologica, 2021)
"Who is a person?" is a question with moral, theological and even legal consequences, but it seems now apparently entangled in intractable puzzles; therefore, it has become frequent to suggest that we should entirely dispense with the idea of "personhood". This essay argues that the notions of "person", and rational "nature" which are essential in theological exploration, cannot be easily discarded from the philosophical vocabulary either. The paper argues that the preferred route of access should preserve the noetic heterogeneity of beings, because it is the current "scientistic" straitjacket that has made very articulation of the question fruitless and impoverished.